Associação do polimorfismo ACTN3 R577X (RS1815739) com respostas inflamatórias e termografia em atletas de futebol - Miller Gomes de Assis (2022)
Genetic factors play a significant role in athletic performance, among these, the ACTN3 gene polymorphism has shown that it can influence athletic performance and skeletal muscle functionality. The aim of the study was to verify possible associations of the genetic profile for the ACTN3 R577X (rs1815739) gene with inflammatory responses, muscle damage and thermography in the pre, 24 and 48 hours after training with a predominance of eccentric actions in Brazilian soccer athletes. Forty-six male soccer athletes from the Under 20 category and with at least 06 years of experience in systematic soccer training were submitted to the study. Subjects were genotyped for the ACTN3 gene and then divided into groups according to their genotype. DNA was extracted from 500 μl of whole blood collected on the first day of the study using a salting out method and the quality and integrity of the sample were tested by spectrophotometry (Nanodrop, Thermo Fisher Scientific GE, MA, United States). For C-Reactive Protein concentrations, the ECO F hs-PCR test was used in the F200 ECO® equipment. For the concentrations of Creatine Kinase, the Simplex ECO POC tests were used in the Simplex ECO® equipment. Thermograms were captured using a thermal imager (FLIR®, T1020, Stockholm, SE) with a measurement range of -20 to +120°C, accuracy of 1%, sensitivity ≤ 0.02°C, infrared spectral band of 7, 5μm to 13μm, 30Hz refresh rate, with autofocus and FULL HD resolution. Two thermograms (posterior and anterior view of the lower limbs), CK and CRP measurements were performed before, 24 and 48 hours after the protocol was carried out. Thermograms were selected and visualized in specific software (APOLLO®, version 1.0, BR). Two-way ANOVA was used and showed that there was a significant interaction between genotypes and CK concentration over time (F = 2.52, p = 0.001, η2 = 0.042, and in the XX group CK concentrations were higher at 48 hours compared to the RR and RX groups (p<0.01), demonstrating that there was a significant interaction between genotypes and skin temperature in the Hot Zone over time (F = 8.71, p < 0.01 , η2 = 0.17), and in the XX group the skin temperature was higher per pixel at 48 hours compared to the RR and RX groups (p<0.02). of CRP over time (F = 6.54, p < 0.01, η2 = 0.29) and in the XX group the CRP concentrations were higher at 48 hours compared to the RR and RX groups (p<0 .01).The conclusion of the study suggests that ACTN3 XX subjects have higher CK, CRP and Skin Temperature activity compared to RR and RX subjects post-training ex centric, showing greater inflammatory response and delay in the acute phase, so XX individuals would need a longer recovery time between training sessions and distribution of training content in order to avoid overtraining and muscle injuries.